The meniscofemoral ligament - Gupte, C. M.; Jeevan, D.; Bull, A. M. J.; Amis, A. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A cadaveric study of ovine stifles was performed to examine the contribution of the meniscofemoral ligament to the cranio-caudal and internal-external rotatory laxity of this joint in sheep.Twenty ovine stifles were harvested, denuded of muscular attachments, and the femur and tibia fixed in bone pots. These were inserted into a four degree-of-freedom rig incorporated into a materials testing machine. Forces up to a maximum of 100N were applied in the cranial and caudal directions, and the resultant translations and coupled rotations measured. Tibial internal and external rotations in response to a 6Nm torque were also measured. These parameters were assessed at 30, 60, 90 and 110 degrees of flexion in twenty intact stifles. In ten stifles a small posterior arthrotomy was used to divide the caudal cruciate ligament (CCL), followed by division of the meniscofemoral ligament (MFL). The sequence of division was reversed for a further ten stifles. The effects of each intervention on the above parameters were evaluated.Division of the MFL resulted in an increase in caudal translation at all angles of flexion in both the intact and CCL deficient stifle. There was also an increase in internal rotation of the tibia after application of a 6Nm torque. This was significant at 30 and 110 degrees of flexion in the intact stifle and at all angles of flexion in the CCL-deficient stifle.These results indicate a secondary role for the MFL in the cranio-caudal and internal/external rotatory stability of the ovine stifle joint. This is the first study demonstrating a functional role for the MFL in any species, and may have a bearing on stifle injuries.
Keywords: Knee injury; caudal cruciate ligament; posterior cruciate ligament; meniscofemoral ligament; lateral meniscus; stifle joint